Analysis on Mechanical Properties of FRP Constrained Concrete Core Reinforcement Under Cyclic Load - Zhenlong, Tong; Zenglin, Wu; Dongyu, Yang; Zhongya, Han (European Journal of Computational Mechanics, 2024)
This article aims to analyse the mechanical properties of FRP confined concrete core rods under cyclic loading. By observing the behaviour characteristics of FRP confined concrete core rods under different cyclic loads, the influence of FRP confinement on concrete cyclic loading is analysed. Based on theoretical analysis, this article establishes a corresponding mechanical model and analyses the response mechanism of FRP constraints to concrete cyclic loads through simulation calculations. Through experimental research and theoretical analysis, it is possible to fully understand the performance of new composite structural materials. The research results of this article indicate that the confinement of FRP bars can significantly improve the compressive strength of concrete specimens. At a constraint ratio of 20%, the compressive strength of the specimen increased by 30% compared to the unconstrained ratio; At 40%, the compressive strength increased by 50%, therefore, FRP confinement can significantly improve the ductility of concrete and reduce fatigue damage under cyclic loading. Through this research method, important evidence can be provided for the application of concrete in practical engineering.